(untitled) (Canadian Oncology Today, 2025)
Neuroendocrine tumours (NETs) represent a rare entity, with various anatomic primary tumour sites, three different grades, a functional or non-functional status, and differences in somatostatin receptor expression, making NETs a heterogeneous disease. The management of these tumours is challenging and varies from a simple watch-and-wait strategy to more complex multi-modality treatment combinations. The choice of treatments depends on the previously mentioned factors. NETs most frequently arise from the gastro-entero-pancreatic (GEP) tract. The article reviews the classification, diagnosis, and staging of well-differentiated GEP-NETs, and discusses different therapeutic options.